Menapaki Jejak Lansekap Budaya Sekitar DAS Oos Jinah - KOHDRATA, NANIEK; UTAMI, NI WAYAN FEBRIANA; SEMARAJAYA, COKORDA GEDE ALIT (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Tracing the Cultural Landscape around Oos Jinah Watershed The research aims to identify the potential of Bali cultural landscape that have conservation values. It is located in Oos Jinah River Basin region for the first year of the study. Descriptive qualitative method is used to capture the cultural landscape spectrum that is relatively complex. Analysis of the landscape potentials use Kozlowski (2011) landscape category appraiser which includes Shape, Structure, Function, Value, Evolution, and Origins. Cultural landscape potentials recorded include the Kusamba traditional salt-making process. It has unique salt crystals harvesting technique, compare to method use in Madura island. Kamasan paintings style stores a process of cultural transformation in its production process. Semarapura town has buildings that leave traces of architecture that can show the development of the city. Temple compound of Pura Taman Sari, Pura Penataran Agung, and Pura Dalem Segening refers to the history of Klungkung kingdom. Garden of Puta Taman Narmada Bali Raja in Tamanbali - Bangli, relates to the history and descendants of Tirta Harum Tamanbali, and the Klungkung kingdom as well. The potential of the cultural landscapes and the intangible heritage objects in Klungkung and Bangli show the diversity and uniqueness that benefit men’s life.